União africana: desafios políticos e perspectivas de cultura no limiar do século XXI - Silva, Joilson de Araujo Martins Andrade (2013)
Objectives This study aims to perform preliminary analyses of this international organization of African states. Reflecting the tensions and stereotypes directed to Africa and their descendants by the media, amid polarized positions ("afro-pessimistic" and "African-optimistic"), as well as presenting topics, debates and proposals before the interdisciplinary field of Contemporary African Studies. Reasons We selected and proposed observations about topics from the African e-Journal, titled Pan African News Agency, Panapress, in its "AU Dossier", a large collection of daily news available to us through the internet. We also used incorporations and partial selections from other sources, such as reports from the AU Assembly of Heads of State and Government, from the decisions of the Executive Council of the AU Commission (2002-2009) and some images from "Dossier Pictures" or "Panapress Pictures" (2001-2009) - in electronic formats - and the" Pan-African Dossier" (1900-1978) from I CIAD (OIF / UA) - in printed. Hypothesis Since the political glances about Africa changes, we extend our attention to relevant cultural perspectives of pan-Africanism. Its immersion and dialogues with demonstrations by the "non-alignment", the consequences of stagnation and subordination of African states, as well as aspects that outlined the historical moment treated as African renaissance, its factors as NEPAD, the AU, its actors Moammar Gadhafi, Thabo M'Beki, Amara Essy, Alpha Konaré, among others. Theoretical and methodological aspects We opted for an analytical position that goes beyond "borders" between politics and culture. A vision that transposes disciplinary visions advancing in the search and construction of transdisciplinary knowledge, in the fields of History and International Relations. We spoke about the "South Atlantic" and the approaches to the "Epistemologies of the South", it was possible to observe Diasporic authors and African actors, who often get little recognition in Western analyses. The sources contemplate connections between history and culture, opens dialogue about analytical dimensions of micro and macro-history, since they revealed dynamics and diversities in electronic media produced in the continent, possibilities of analyzes beyond the "afropessimistic" visions. Results These perspectives led to a greater perception of inclusiveness, awareness and understanding of international relations. They revealed the understanding that these relations between states, coexist with interpersonal and social relations, in addition to providing for new proposals to cultural, political and anti-racist struggles for reflection and awareness of diversity